Line x tester analysis of combining ability in new genotypes of bivoltine silkworm (Bombyx mori) - RAJALAKSHMI, E; CHAUHAN, T P S; THIAGARAJAN, V; LAKSHMANAN, V; KAMBLE, C K (The Indian Journal of Agricultural Sciences, 2013)
A line X tester analysis was carried out, involving 8 newly evolved genotypes, 2 testers and 16 hybrids of bivoltine silkworm (Bombyx mori L.) for assessing the combining ability in respect of cocoon yield by number and weight, single-cocoon weight, single-shell weight, shell ratio (%) and filament length. All the characters studied were controlled by additive but predominantly by non-additive gene action, ’CNR 14’ with positive general combining ability (gca) effect for all the 6 characters studied proved the best general combiner, followed by ’CNR 12’ and ’CNR 13’ for 5 characters, ’CNR 15’ for 4 characters and ’CNR 16’ for 3 characters, ’CNR 13’ and ’CNR 16’ for single-cocoon weight, ’CNR 12’, ’CNR 14’ and ’CNR 16’ for single-shell weight, ’CNR 12’ and ’CNR 15’ for shell ratio (%)and ’CNR 14’ for filament length were found to be the best general combiners with highly significant positive gca effects. ’CNR 16’ X ’NB 4D2’ was considered the best hybrid, as it recorded signiticant effects of specific combining ability (sea) for 3 characters out of the 6 studied.